PENGARUH PENERAPAN MODEL PEMBELAJARAN SIKLUS 5E MENGGUNAKAN MODUL TERINTEGRASI NILAI-NILAI KARAKTER TERHADAP PENCAPAIAN KOMPETENSI SISWA KELAS X SMAN 16 PADANG - M. A lfajri Syam (Universitas Negeri Padang, 2014)
Achievement of competencies students have not shown optimal results. This is because not applied learning models that generate student interest and no teaching materials integrated character values. One solution to overcome this problem is to adopt a model of 5E learning cycle using teaching materials in the form of an integrated module of character values. The purpose of this study was to determine the effect of the application of the model using the 5E learning cycle integrated module of character values to the achievement of student competencies class X. This research is a quasi experimental study. The research design used was Randomized Control Group Designed Only. The population of this study was all class X in SMAN 16 Padang listed in Semester 1 Academic Year 2013/2014. In this study two classes are taken as the sample grade experimental class and control class. This study used a purposive sampling technique and was selected as the experimental class class X3 and X2 class as a control class that each class has 32 students. To get the value of the cognitive aspects of testing. Meanwhile, to get the value of the affective and psychomotor aspects of the non-test techniques used in the form of an assessment rubric. Data analysis was performed using t-test with a significance level of 0.05. Based on the results of data analysis, it can be concluded that the achievement of students in the experimental class competence higher than the control class in the three aspects of the assessment. It can be concluded that the application of the model using the 5E learning cycle integrated module character values have a significant influence on the achievement of competence tenth graders X students of SMAN 16 Padang